LITERATUR REVIEW : DAMPAK DESENTRALISASI FISKAL TERHADAP TATA KELOLA DAN KINERJA PEMERINTAH DAERAH DI INDONESIA - Erizona, Wawan; Frinaldi, Aldri; Magriasti, Lince; Hendra Naldi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Fiscal decentralization is a major component of Indonesia’s governance reform, intended to improve public service efficiency, strengthen accountability, and promote equitable development. This paper describes the relationship between fiscal decentralization, local government capacity, and accountability, as well as their implications for public service quality, poverty alleviation, and fiscal disparities. Using a descriptive literature-based approach, this study synthesizes empirical findings from national and international peer-reviewed research relevant to the Indonesian context. The findings reveal that fiscal decentralization can enhance public service delivery and regional development when accompanied by strong institutional capacity, robust accountability systems, and performance-based fiscal transfer mechanisms. Conversely, in regions with weak administrative capacity, decentralization tends to increase recurrent spending and potential corruption. Policy reforms in fiscal design and local governance are essential to ensure the effectiveness and equity of fiscal decentralization.